Epidemiology of Surfing-related Injuries in South Korea: Type, Location, and Mechanism - 신승우(Seung Woo Shin); 이주성(Juseong Lee); Junghoon Kim (The Asian journal of kinesiology, 2022)
OBJECTIVES Although the surfing-related injuries has been increasing with growing numbers of recreational surfers worldwide, lack of epidemiological evidence about the surfing injuries. Therefore, the purpose of this study was to identify the types and mechanism of injury in recreational surfers. We also aimed to determine the differences in the type and mechanism of injury according to surfer’s characteristics (sex and surfing experience). METHODS A total of 227 participants (149 male and 78 female) were recruited and analyzed for this study. To identify the surfing-related injuries, we investigated the types, locations, season, and mechanism of injury using a questionnaire. RESULTS The highest frequency of injury was found in skin, followed by muscle and tendon, and joints. There were not significant differences in the injury types according to the sex and surfing experience (≤12 versus >12 months). An upper limb and arm injury was significantly higher in male (p<0.01) and the torso injury was higher in female (p<0.05). Moreover, the less experience (≤12 months) of surfing was associated with higher rates of injury caused by falling or collision with other surfers. CONCLUSIONS To the best of our knowledge, this is the first epidemiological study presented the surfingrelated injury among Korean population. We found the injuries mainly occurred on the skin, and muscle and tendon. In addition, our results suggest that surfers with insufficient experience may be vulnerable to injuries from falls and contact with other surfers. Consequently, these epidemiological data may be utilized to prevent and manage the injury in surfers according to surfer’s characteristic and experience. KCI Citation Count: 0